MULTISCALE CORRELATION OF MICROVASCULAR CHANGES ON OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY WITH RETINAL SENSITIVITY IN DIABETIC RETINOPATHY. Issue 2 (February 2022) - Levine, Emily S.; Moult, Eric M.; Greig, Eugenia Custo; Zhao, Yi; Pramil, Varsha; Gendelman, Isaac; Alibhai, Agha Y.; Baumal, Caroline R.; Witkin, Andre J.; Duker, Jay S.; Fujimoto, James G.; Waheed, Nadia K.
Abstract : Purpose: To assess global, zonal, and local correlations between vessel density changes measured by optical coherence tomography angiography and retinal sensitivity measured by microperimetry across diabetic retinopathy severity. Methods: Diabetic patients and nondiabetic controls underwent optical coherence tomography angiography imaging and microperimetry testing. Pearson's correlation was used to assess associations between average sensitivity and skeletonized vessel density (SVD) or foveal avascular zone area centrally. Linear mixed effects modeling was used to assess relationships between local SVD measurements and their spatially corresponding retinal sensitivity measurements. Results: Thirty-nine eyes from 39 participants were imaged. In all slabs, there was a statistically significant positive correlation between retinal sensitivities and SVDs on both global and zonal scales. No statistically significant correlation was found between central retinal sensitivities and the foveal avascular zone areas. Assessment of 1, 136 spatially paired retinal sensitivity and SVD measurements revealed a statistically significant local relationship; this seemed to be driven by eyes with proliferative diabetic retinopathy that had reduced retinal sensitivities. Conclusion: This study supports positive correlations between SVD and retinal sensitivity at global and zonal spatial scales in diabetic eyes. However, our analysis did not find evidence of statistically significant correlations between retinal sensitivity and SVD on a local scale until advanced diabetic retinopathy. Abstract : Vessel density changes measured by optical coherence tomography angiography and microperimetry-derived retinal sensitivity from patients with diabetic retinopathy correlated globally and zonally, as well as locally at reduced sensitivities in late disease.